Effects of successive running and cycling on the release of atrial natriuretic factor in highly trained triathletes - Galy, O.; Hue, O.; Peyreigne, C.; Boussana, A.; Chamari, K.; Libicz, S.; Couret, I.; Le Gallais, D.; Prefaut, C. (The Journal of Sports Medicine and Physical Fitness, 2004)
Aim: To evaluate the influence of successive running and cycling on both exercise-induced arterial hypoxemia (EIAH) and atrial natriuretic factor (ANF) release, 5 triathletes performed 2 separate exercise trials. Methods: One trial consisted of a 20-min+20-min successive cycle-run exercise (C1-R2) and the other consisted of a 20-min+20-min successive run-cycle exercise (R1-C2). Arterial oxygenation (PaO2) and ANF were determined at pre-exercise, at the end of each 20-min segment of exercise and after 10 min of recovery. Results: EIAH was noted during C1-R2 and R1-C2 trials. A higher EIAH was observed during running compared with cycling performed in the 1st position (R1 vs C1) in the succession. In contrast, no difference was observed between successive running and successive cycling (R2 vs C2), (-10.6±7.0 vs -15.6±4.0 mmHg for C1-R2 and -20.9±6.0 vs -16.2±2.4 mmHg for R1-C2). ANF showed no difference between cycling and running performed in first position, whereas a significantly lower ANF was observed during successive cycling compared with successive running (C2 vs R2) (19.9±3.72 vs 36.2±6.4 pmol.l-1). During recovery, neither PaO2 nor ANF plasma returned to baseline level after either trial. Conclusion: This study provides new information on some of the physiological modifications that occur during multi-sports. Specifically, the impact of the modality of the successive exercise on ANF release and body fluid regulation was observed. Cycling as the successive exercise seems to cause lower ANF release than does running.